2019
DOI: 10.1556/004.2019.031
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of porcine epidemic diarrhoea virus in Hungary – Short communication

Abstract: Porcine epidemic diarrhoea virus (PEDV) is an emerging enteropathogen, causing great economic losses in the pig industry. After many years of quiescence, PEDV was detected in Hungary in 2016 with a recombination in its S gene. In order to determine the extent of this change, an attempt was made to isolate the recombinant PEDV. This study was extended with a variety of samples collected from three separate farms with newly identified PEDV in 2018. The recombinant PEDV from 2016 was isolated successfully along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…However, some breeding herds reported high mortality rates with up to 85% losses in suckling piglets [ 1 ]. Similar outbreaks were observed in several other Central European countries including France, The Netherlands, Italy, Slovenia, Belgium, Romania, Portugal, Spain, and Austria [ 16 – 23 ].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, some breeding herds reported high mortality rates with up to 85% losses in suckling piglets [ 1 ]. Similar outbreaks were observed in several other Central European countries including France, The Netherlands, Italy, Slovenia, Belgium, Romania, Portugal, Spain, and Austria [ 16 – 23 ].…”
Section: Introductionsupporting
confidence: 76%
“…1 ). Close relatives are three virus strains reported in 2019, two from Hungary [ 16 ] (accessions MH593900 and KX289955) and one from France (accession MN056942).
Fig.
…”
Section: Case Presentationmentioning
confidence: 99%
“…When the complete genome sequences were analysed, the (Guo et al, 2018;Zhang et al, 2018 SeCoV reported in these isolates was described previously (Valkó et al, 2017(Valkó et al, , 2019 and might provide some advantages, as the S protein is a key target for PEDV neutralizing antibodies (Li et al, 2017;Okda et al, 2017). Besides, the comparison of the sequences of this recombinant region indicated that the SP4 subgroup clusters together with the more modern SeCoV strains (after 2009), but not with the older Spanish ones (1993)(1994)(1995)(1996)(1997)(1998)(1999), reinforcing the notion F I G U R E 2 Phylogenetic analysis of the porcine epidemic diarrhoea virus (PEDV) and the swine enteric coronavirus (SeCoV) based on the complete S-gene sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In order to clarify the phylogenetic origin of the S-gene of the recombinant SeCoV with respect to those of the PEDV strains, a phylogenetic tree was constructed using the S-gene sequences from this study and those of the complete genome of the three SeCoV from Italy 2009 (Boniotti et al, 2016), Germany 2012 (Akimkin et al, 2016) and Central Eastern Europe 2016 (Belsham et al, 2016) and PEDV available in GenBank (Figure 2) (Valkó et al, 2017(Valkó et al, , 2019 and also by the -1993 (1), EGV-1993 (2), SG1-1994 (3), VA-1994 (4), MU2-1998 (5), AYL-1999 (6), 1480-2014 7, 1613-2015 as a positive control for PEDV (8), positive control for TGEV (9) and nontemplate control (10) are shown associated with this recombinant virus have been described as less severe than those of PEDV, with a significantly lower mortality (Belsham et al, 2016;Boniotti et al, 2016) and would allow the infection to pass unnoticed in a certain number of farms. Moreover, the use of PEDV diagnostic tests targeted at the S-protein, including ELISA (Carvajal, Lanza, Diego, Rubio, & Cámenes, 1995;van Nieuwstadt & Zetstra, 1991) or PCR-based assays (Kim et al, 2001), which is a naturally occurring mutant of the TGEV with a great deletion in its genome and produces a mild respiratory disease in pigs (Pensaert, Callebaut, & Vergote, 1986), provide pig population cross-immunity against the enteric virus TGEV due to their similarity.…”
Section: Ta B L E 2 Primers Used In the Amplification Of The S-genementioning
confidence: 99%
See 1 more Smart Citation